Effect of hydroquinone and copper coated urea on ammonia volatilization loss and n mineralization from tropical soil: laboratory study - Junejo, Nasima; Yusop, Mohd Khanif; Dharejo, Khalil Ahmed; Abdu, Arifin (Academic Journals, 2013)
The faster urea hydrolyses process leads to high amount of ammonia gas emission from urea fertilized fields. Coating of urea with various materials is the most successful strategy to control N losses from urea fertilized fields. A laboratory study was conducted to evaluate the effects of uncoated urea, as compare to urea coated with hydroquinone and Cu on NH3 volatilization loss and rate of urea hydrolysis in soil. The coated urea treatments were prepared by using Cu and hydroquinone solutions with a fluidized bed coating machine. Two experiments were carried out to evaluate the coated urea treatments labelled as UCu (Cu coated urea) and UHY (Hydroquinon urea). Both experiments were carried out on a sandy soil named as Serdang series. The soil was characterized for its properties by standard methods. In the first experiment the coated urea was evaluated for ammonia volatilization loss by using closed chamber force draft technique. Simultaneously, an incubation experiment was conducted to evaluate the effect of hydroquinone and Cu coated urea treatments for their hydrolyses rate or mineralization process. It was estimated by the results that ammonia volatilization from Hydroquinon coated urea treated soil reduced 25% however, Cu coated urea showed 30% reduction in ammonia volatilization loss as compare to uncoated urea. In incubation experiment recovery of urea from soil was 50% more in coated urea as compare to uncoated urea. It is concluded that coating of urea with urease inhibitors can reduce successfully the ammonia volatilization loss and increased the recovery of urea either coated by Cu or hydroquinone.